Relationship Between Trauma Sustained at Unloading and Carcass Bruise Prevalence in Finished Cattle at Commercial Slaughter Facilities - T. Lee; C. D. Reinhardt; S. J. Bartle; Christopher Vahl; M. Siemens; E. F. Schwandt; D. U. Thomson (Kansas Agricultural Experiment Station Research Reports, 2017)
Bruising in cattle can be an indicator of poor animal welfare, as well as a significant cause of economic loss due to decreased carcass value. Previous literature suggests sources of trauma causing bruising in beef carcasses include horn prevalence, rough transport conditions, cattle handling techniques, cattle temperament, and vehicle design; however, evidence of correlations between such trauma and actual carcass bruising is limited. The objective of this study was to evaluate the relationship between trauma sustained at unloading and carcass bruise prevalence in finished cattle at commercial slaughter facilities.
Keywords: animal welfare; bruising; finished cattle